Transscleral Photodynamic Therapy with a Chlorin e6 Photosensitizer in a Rabbit Experimental Model of an Intraocular Mass Lesion: TS-PDT in experimental ocular mass lesion model - Boiko, Ernest V.; Samkovich, Elena V.; Panova, Irina E.; Shevchenko, Sergey B.; Vorobyev, Sergey L.; Kalashnikova, Elizaveta S.; Masian, Elizaveta A.; Gvazava, Victoria G. (Journal of Lasers in Medical Sciences, 2025)
Introduction: In vivo modeling of intraocular neoplasms remains challenging due to the limitations of conventional methods, such as the poor viability of xenografted B16 melanoma cells, the need for immunosuppression, and discrepancies between histopathological features and those of human uveal melanoma. Developing a biologically relevant, reproducible model for transscleral photodynamic therapy (TS-PDT) using chlorin-based photosensitizers is essential, particularly to assess radiation penetration depth and the safety profile of the method. Methods: A model of an intraocular mass was created using an alloplant—an acellular biomaterial derived from the kidney capsule—implanted into the suprachoroidal space of rabbit eyes in both pigmented and non-pigmented variants. TS-PDT was performed using chlorin e6 (2.5 mg/kg) and a 660 nm laser (0.17 W, 10 minutes). Monitoring included ultrasound imaging, fundus photography, and histological analysis conducted 41 days post-treatment. Results: The alloplant maintained structural integrity and elicited only minimal inflammatory response. The absence of thermal damage to the sclera confirmed the safety of the selected treatment parameters. In the choroid, focal thrombosis, vascular ectasia, and stromal fibrosis were observed. Retinal necrosis overlying the alloplant (penetration depth>3 mm) indicated sufficient radiation penetration. The pigmented model demonstrated accumulations of pigmentladen macrophages, replicating the optical properties of melanin-containing tissues. Conclusion: This alloplant-based model enables standardized TS-PDT investigation with clinical relevance and confirmed safety. The selective effect on deep ocular tissues supports TS-PDT’s potential in eye-preserving tumor therapy. Future directions include studying neovascularization and optimizing treatment protocols.